Young People Transitioning out of Alternative Care in Egypt: Aftercare Challenges Faced by Non-profit Organizations and the Way Forward - Abdel Hafez, Mai Amr (AUC Knowledge Fountain, 2022)
Young people raised in Care homes face many challenges after they reach 18 years old and have to leave these care homes to be independent and integrate with society. Minimal research is conducted in Egypt on this topic; thus, this study is presented to fill this research gap by answering these research questions: What were the biggest challenges faced by the care leavers? And how can the government and the non-profit sector support in decreasing these challenges? The purpose of the study is focused on the effectiveness of care homes in preparing young people for aftercare and how to provide sustainable service by the government and nonprofit organizations to promote the wellbeing of the care leavers. 17 Semi-structured interviews have been conducted with care leavers, social workers, and child protection experts to gain insights on this issue. The main findings of this study are presented in a life cycle approach with three main themes: pre-leaving care, transition, and post-leaving care. The pre-leaving care factors identified that had a later impact on leaving care, such as frequent placements, the relationship with caregivers, facing stigma since childhood, and overprotecting the females. In the transition phase of leaving care: the preparations and support that some care homes provide to the young people and the experience of leaving from the young people’s perspectives. In The post-leaving phase, many challenges have been identified in several domains such as: housing, life skills, education, employment, relationships, stigma, financial situation, health, mental health, resilience, and relationship with the civil society. The study concludes with recommendations to policy makers and practitioners derived from the data with the aim to increase the effectiveness of care homes in preparing young people for aftercare.